Xinjiang herbal tea exerts immunomodulatory activity via TLR2/4-mediated MAPK signaling pathways in RAW264.7 cells and prevents cyclophosphamide-induced immunosuppression in mice. (10th January 2019) - Bai, Yujia; Jiang, Yunyao; Liu, Tingwu; Li, Fu; Zhang, Jianmei; Luo, Yanyan; Zhang, Liang; Yan, Guilong; Feng, Zuoshan; Li, Xueqin; Wang, Xinfeng; Hu, Weicheng
Abstract: Ethnopharmacological relevance: A multi-herb Chinese medicinal formula consisting of a variety of medicinal and edible materials has long been consumed as a hot drink and immune enhancer for its efficiency to increase disease resistance in Xinjiang, China. However, no fundamental data has been collected associated with traditional consumption. The present work was designed to evaluate the immunostimulatory role of Xinjiang herbal tea (XMT-WE) in RAW 264.7 macrophages and cyclophosphamide (CTX)-induced immunosuppression mice model. Materials and methods: RAW 264.7 cells were treated with various concentrations of XMT-WE. Nitric oxide (NO) levels were determined using Griess reagents, and pro-inflammatory cytokines such as interleukin (IL)-6 and tumor necrosis factor (TNF)-α were investigated with a cytometric bead array kit. The effects on mRNA expression of inducible nitric oxide synthase (iNOS), cyclooxygenase (COX)-2, and TNF-α were investigated. Furthermore, activation of nuclear factor (NF)-κB and AP-1 mitogen-activated protein kinase (MAPK) signaling pathways was investigated. Results: Pre-treatment with XMT-WE significantly increased secretion of NO, IL-6, and TNF-α. In addition, XMT-WE markedly increased expression of iNOS, COX-2, and TNF-α as well as AP-1 and NF-κB translocation from the cytoplasm into the nucleus, which was associated with an increase of phosphorylated ERK, JNK, and p38 as well as membrane receptors such as toll-like receptor (TLR) 2 and TLR4. Moreover, XMT-WE promoted the secretion of interleukin-2 (IL-2) and interferon-γ (IFN-γ) in cyclophosphamide (CTX)-induced immunosuppressive mice. Conclusion: These results indicated that XMT-WE at 50 µg/ml exerts immunomodulatory activity via TLR2/4-mediated MAPK signaling pathways in RAW 264.7 cells. Furthermore, in vivo experiments revealed that XMT-WE at the dose of 50 and 100 mg/kg strongly stimulated inflammatory cytokines. Graphical abstract: